2005
DOI: 10.2118/84609-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Method to Predict and Prevent Asphaltene Deposition in Oilwell Tubings: Field Case

Abstract: Summary The natural state of asphaltenes in petroleum fluids is described as a colloidal system stabilized, to some extent, by the resins that act as peptizing agents. Destabilization of colloidal asphaltenes appears to happen as a result of changes in temperature, pressure, and composition. This can significantly affect the production efficiency of a reservoir during oil recovery. The phenomenon of asphaltene flocculation and deposition in well tubing appears to be influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
5
12
0
Order By: Relevance
“…A few case studies were performed to measure the thickness of the deposited layer in well tubing with diameters of 4.5 and 1.75 in. (Haskett and Tartera 1965;Al-Kafeef et al 2005). In one case, asphaltene deposition in a west Kuwait well was assessed through measurements of flowing wellhead pressure by a pressure gauge, and found to reach one-third of the inner well-tubing radius (Al-Kafeef et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few case studies were performed to measure the thickness of the deposited layer in well tubing with diameters of 4.5 and 1.75 in. (Haskett and Tartera 1965;Al-Kafeef et al 2005). In one case, asphaltene deposition in a west Kuwait well was assessed through measurements of flowing wellhead pressure by a pressure gauge, and found to reach one-third of the inner well-tubing radius (Al-Kafeef et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(Haskett and Tartera 1965;Al-Kafeef et al 2005). In one case, asphaltene deposition in a west Kuwait well was assessed through measurements of flowing wellhead pressure by a pressure gauge, and found to reach one-third of the inner well-tubing radius (Al-Kafeef et al 2005). In another case, with a similar method, the deposit in five different wells of the Hassi Messaoud field in Algeria was measured, and found to reach approximately two-thirds of the inner-tubing radius (Haskett and Tartera 1965).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few case studies have been performed to measure the thickness of the deposited layer in pipes with diameters between 2 and 5 inches, and researches found that the deposit thickness reached between 1/3 and 2/3 of the pipe radius. 8,9 Such excessive deposition greatly reduces production efficiency. As a result, better understanding of the deposition process has been sought through modeling efforts.…”
Section: Introductionmentioning
confidence: 99%